2006
DOI: 10.1007/bf03327571
|View full text |Cite
|
Sign up to set email alerts
|

Challenging previous conceptions of vegetarianism and eating disorders

Abstract: The purpose of this study was to replicate and expand upon previous research that has examined the potential association between vegetarianism and disordered eating. Limitations of previous research studies are addressed, including possible low reliability of measures of eating pathology within vegetarian samples, use of only a few dietary restraint measures, and a paucity of research examining potential differences in body image and food choice motives of vegetarians versus nonvegetarians. Two hundred and fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…ore females than males followed a vegetarian diet, and more adolescents who considered they had a healthy diet were VE ( It was found that females were more 2.89 times more likely to be VE than males, when the possible variables Discussion relationship between vegetarianism and ED risk behavior in a large sample of adolescents from public schools in São Paulo, Brazil. Out of the total, 4.1% (n=48) considered themselves to be vegetarian, and of those 70.8% were prevalence of vegetarianism in other studies among adolescents ranged between 2.5% and 6% and, like the present study the majority of the vegetarian adolescents were female; on average, the prevalence of female VE was over 70% 5,6,8,9,20,21 adolescents who follow a vegetarian diet may be that they are more concerned about their body weight and shape 5,22 .…”
Section: Resultssupporting
confidence: 53%
“…ore females than males followed a vegetarian diet, and more adolescents who considered they had a healthy diet were VE ( It was found that females were more 2.89 times more likely to be VE than males, when the possible variables Discussion relationship between vegetarianism and ED risk behavior in a large sample of adolescents from public schools in São Paulo, Brazil. Out of the total, 4.1% (n=48) considered themselves to be vegetarian, and of those 70.8% were prevalence of vegetarianism in other studies among adolescents ranged between 2.5% and 6% and, like the present study the majority of the vegetarian adolescents were female; on average, the prevalence of female VE was over 70% 5,6,8,9,20,21 adolescents who follow a vegetarian diet may be that they are more concerned about their body weight and shape 5,22 .…”
Section: Resultssupporting
confidence: 53%
“…In fact, most data show that plant-based diets are not only great for the environment [13,50], but also human health [13,116,142], and they may promote performance enhancement [123,143]. While some athletes may use vegan diets to mask an eating disorder, there is no evidence that vegan or vegetarian diets cause eating disorders [144]. Considering that a reduction in meat, using more plant-based approaches, is effective in decreasing environmental impact does not mean that athletes must turn vegan.…”
Section: Eat As If You Could Save the Planet And Win!mentioning
confidence: 99%
“…The findings have demonstrated that vegetarian diet is associated with higher levels of cognitive restraint [17]. Some studies have presented that individuals following a vegetarian diet endorses higher levels of cognitive restraint that those following an omnivorous diet [18], whereas other studies have found no difference in cognitive restraint between these both groups [17,19,20]. Although orthorexia nervosa shares a key component with cognitive restraint (self-imposed restriction of allowed food) [10], these both should be considered as distinct constructs.…”
Section: Introductionmentioning
confidence: 97%